2009
DOI: 10.1002/adfm.200801675
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcated Mechanical Behavior of Deformed Periodic Porous Solids

Abstract: The transformation of periodic microporous structures fabricated by interference lithography followed by their freezing below glass transition is described. Periodic porous microstructures subjected to internal compressive stresses can undergo sudden structural transformation at a critical strain. The pattern transformation of collapsed pores is caused by the stresses originated during the polymerization of acrylic acid (rubbery component) inside of cylindrical pores and the subsequent solvent evaporation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…An analytical mechanics model, validated by FEA, is developed to identify the mechanism of these enhancements. Although mechanical simulations for large compressive deformation in 2D-ordered porous polymers have been studied 23 , deformation mechanics of 3D-ordered porous elastomers under stretching is not well-known. Th e symmetry of 3D polymer structure fabricated from PnP is similar to body-centred tetragonal with sub-micron lattice parameters 20 .…”
Section: Fabrication Of 3d Pdmsmentioning
confidence: 99%
“…An analytical mechanics model, validated by FEA, is developed to identify the mechanism of these enhancements. Although mechanical simulations for large compressive deformation in 2D-ordered porous polymers have been studied 23 , deformation mechanics of 3D-ordered porous elastomers under stretching is not well-known. Th e symmetry of 3D polymer structure fabricated from PnP is similar to body-centred tetragonal with sub-micron lattice parameters 20 .…”
Section: Fabrication Of 3d Pdmsmentioning
confidence: 99%
“…In particular, instabilities in periodic porous structures comprising square and triangular arrays of circular holes have been found to lead to the transformation of the pores into ordered arrays of high-aspect ratio (almost closed) ellipses (Mullin et al, 2007;Zhang et al, 2008;Singamaneni et al, 2009) and have been demonstrated to be instrumental for the design of phononic switches Wang and Bertoldi, 2012), color displays (Li et al, 2012) and materials with unusual properties such as large negative Poisson's ratio .…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanical behavior of patterned polymeric materials at large deformation [1][2][3][4][5][6][7][8][9][10][11] is of signifi cant importance for practical applications in smart membranes, [ 12 ] tunable photonic/phononic crystals, [ 13 ] adjustable microlenses, [ 14 , 15 ] and porous templates for cell areas (72 mm × 10 mm) at the top and bottom represent the sample holding areas during the tensile test. In order to describe the sample geometry and the honeycomb structure, two different Cartesian coordinators were employed.…”
Section: Introductionmentioning
confidence: 99%